PERAN TABLOID DAN MEDIA SOSIAL PEMERINTAH KABUPATEN ACEH BARAT DALAM MEMBENTUK BERITA KEHUMASAN - Kasyfi Haq Putra Marwandi; Firman Perlindungann; said Fadhlain (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2021)
Media communication is a basic right of the community in accessing information, by applying the principle of transparency and accountability in the implementation of government. The role of local media as a means of information and communication in development can contribute to setting the public agenda, capturing independent aspirations from various news and providing accurate, reliable information and in a series of regional development implementations. This scientific work is the result of an analysis of the Student Internship Program which is carried out for one semester (6 months) starting in February-August 2021. The method used is the survey method as a descriptive study (qualitative approach). The location of the internship is carried out at the West Aceh Regency Communication, Information and Encryption Service (Diskominsa). The results of the study show that the media can provide education and create an open and critical society. Through online media and tabloid media, it acts as a means of information in conveying news of regional development in a factual, open and reliable manner.